2013
DOI: 10.1684/epd.2013.0591
|View full text |Cite
|
Sign up to set email alerts
|

Management and monitoring of patients treated with zonisamide: the OZONE study

Abstract: To characterise patients treated with zonisamide in everyday practice and describe the effectiveness and tolerability of treatment. Methods. This was an observational, longitudinal, naturalistic study, conducted by neurologists in France. Patients who had started zonisamide treatment at least three months prior to inclusion were eligible. Data were collected at routine consultations at inclusion (Visit 1) and three to six months later (Visit 2). At Visit 1, investigators documented epilepsy-related variables b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…The primary outcome of this study was impressive with more than approximately 80% of patients achieving ≥50% reduction in seizure frequency, whereas seizure freedom was achieved in approximately 41% of patients after 24 weeks of zonisamide treatment. The responder rate and proportion of patients who achieved seizure freedom with zonisamide were 40.9% and 15%, respectively, in ZEUS; 12 79% and 34% in ZADE study; 13 65.9% and 25.6% in OZONE study; 14 and 79.7% and 43.6% in ZOOM study. 15 This difference may be attributable to inclusion of patients with less severe and less refractory epilepsies in our study.…”
Section: Discussionmentioning
confidence: 87%
“…The primary outcome of this study was impressive with more than approximately 80% of patients achieving ≥50% reduction in seizure frequency, whereas seizure freedom was achieved in approximately 41% of patients after 24 weeks of zonisamide treatment. The responder rate and proportion of patients who achieved seizure freedom with zonisamide were 40.9% and 15%, respectively, in ZEUS; 12 79% and 34% in ZADE study; 13 65.9% and 25.6% in OZONE study; 14 and 79.7% and 43.6% in ZOOM study. 15 This difference may be attributable to inclusion of patients with less severe and less refractory epilepsies in our study.…”
Section: Discussionmentioning
confidence: 87%
“…Zonisamide has a clear advantage over ethanol in that it has been proved relatively safe, effective, and well-tolerated in long-term treatments as monotherapy or adjunctive therapy (115,116). Additionally, zonisamide has a pharmacokinetic characteristic favorable for clinical use.…”
Section: Zonisamidementioning
confidence: 99%
“…The results of the pivotal add-on studies are shown in Table 1. Long-term efficacy of ZNS as add-on therapy in adults with focal epilepsy could be documented both in open-label extension studies completing fixed-dose, randomized, double-blind clinical trials (Brodie 2004;Wroe et al 2008) and in several openlabel real-world studies (Dupont et al 2010(Dupont et al , 2013Hamer et al 2016;Helmstaedter et al 2011). In these studies, responder rates and proportions of seizure-free patients were 40.9-44.2% and 15.0-15.9% in the ZEUS study (281 patients, follow-up 19 weeks) (Dupont et al 2010), 79% and 34% in the ZADE study (207 patients, follow-up 4 months) (Helmstaedter et al 2011), 65.9% and 25.6% in the OZONE (Dupont et al 2013), and 79.7% and 43.6% in the ZOOM study (100 patients, follow-up 6 months) (Hamer et al 2016).…”
Section: Clinical Studiesmentioning
confidence: 99%